RANCANG BANGUN MESIN AMPLAS DENGAN SISTEM MEKANIS BELT - Arief Ikma Putra; Yuli Yetri; Maimuzar Maimuzar (Jurnal Teknik Mesin, 2018)
Sanding work is a stage that is carried out before entering the finishing process to remove defects and smooth the surface of the object. The main purpose of making sanding machines with this mechanical belt system is to help and simplify the sanding process. The method for making sanding machines with mechanical belt systems is: needs analysis, problem analysis and specifications, problem statements, concept design, technical analysis, work drawing and tool testing. The results of the design of the sanding machine with a mechanical belt system are obtained in the form of a design with a working drawing of a sanding machine with a mechanical belt system. The sanding machine with a mechanical belt system has specifications that are 500 mm long, 350 mm wide, and 1400 mm high. The source of driving the sanding machine with a mechanical belt system is an electric motor ¼ HP with 2800 rpm rotation. The transmission system uses pulleys. The sanding machine with a mechanical belt consists of several components, namely the engine frame, electric motor, pulleys, tables, belt aplas, and adjustment of the belt strength of the sandpaper. The belt pulley used is from ST 37 with a diameter of 25 mm and pulley rotation of 2800 rpm. Frame construction uses hollow iron measuring 40x40x3 mm from ST 37 material. The table uses 590x150 acrylic material.